Influence of different sources and fiber levels in the diet of juvenile pacu (Piaractus mesopotamicus) on the growth performance, somatic parameters and proximate composition (Revista de Ciências Agroveterinárias, 2021)
The objective of the present work was to evaluate the effects of soybean husk and rice husk on the performance, somatic parameters and proximate composition of whole fish of juvenile pacu (Piaractus mesopotamicus). For this, 216 juveniles of pacu were used, with an average weight of 6 ± 0.81 grams, distributed in 18 water tanks, in a recirculation system. Six diets were formulated containing levels of 10, 13 and 15% of NDF inclusion for each fiber source, with 30% of crude protein and 3,000 Kcal Kg-1 of digestible energy. It was observed that the levels of 10 and 13% of NDF promoted the best results for performance variables such as final weight, weight gain, specific growth rate and final length. It was also possible to observe that fish fed a diet containing 10% NDF had a higher carcass yield, but no difference was observed between the somatic, hepatosomatic and intestinal quotient digestive indexes. However, no significant differences were observed for the proximate composition variables of whole fish. Thus, it can be concluded that up to 13% of NDF does not affect the zootechnical performance, carcass quality, and somatic parameters of the fish.
Keywords: Co-products; soy husk; rice husk; neutral detergent fiber; zootechnical performance